Educational differentials in key domains of physical activity by ethnicity, age and sex: a cross-sectional study of over 40 000 participants in the UK household longitudinal study (2013–2015). Issue 1 (20th January 2020) - Fluharty, Meg E; Pinto Pereira, Snehal M; Benzeval, Michaela; Hamer, Mark; Jefferis, Barbara; Griffiths, Lucy J; Cooper, Rachel; Bann, David
Abstract : Objectives: To assess whether educational differentials in three key physical activity (PA) domains vary by age, sex and ethnicity. Design: National cross-sectional survey. Setting: UK. Participants: Altogether 40 270 participants, aged 20 years and over, from the UK Household Longitudinal Study with information on education, PA and demographics collected in 2013–2015. Outcome measures: Participation in active travel (AT), occupational activity (OA) and leisure time physical activity (LTPA) at the time of assessment. Results: Lower educational attainment was associated with higher AT and OA, but lower weekly LTPA activity; these associations were modified by sex, ethnicity and age. Education-related differences in AT were larger for women—the difference in predicted probability of activity between the highest and the lowest education groups was −10% in women (95% CI: −11.9% to 7.9%) and −3% in men (−4.8% to –0.4%). Education-related differences in OA were larger among men −35% (-36.9% to –32.4%) than women −17% (-19.4% to –15.0%). Finally, education-related differences in moderate-to-vigorous LTPA varied by ethnicity; for example, differences were 17% (16.2% to 18.7%) for white individuals compared with 6% (0.6% to 11.6%) for black individuals. Conclusions: Educational differences in PA vary by domain and are modified by age, sex and ethnicity. A better understanding of physically inactive subgroups may aid development of interventions to both increase activity levels and reduce health inequalities.